(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This study examines the regulatory challenges faced by e-commerce and online trading in the digital age. The rapid expansion of digital markets has introduced complex regulatory issues that vary across regions. By comparing global regulations, this study highlights how governments worldwide address concerns related to cybersecurity, consumer protection, taxation, cross-border trade, and platform accountability. Special attention is given to the strategies adopted by different countries to ensure secure online transactions, safeguard consumer rights, and promote fair competition in the global digital marketplace.